Are we there yet? A signature pedagogy for sports coaching. Issue 2 (15th March 2021) - Carson, Fraser; Walsh, Julia
ABSTRACT: (Shulman, L. 2005a. "Signature Pedagogies in the Professions." Daedalus 134 (3): 52–59) presented a call to action for disciplines to rethink how neophytes are prepared for the work place, asking professions to interrogate their signature pedagogy. While some pedagogies are more mature, particularly those with well forged professional pathways and publically recognised ways of thinking and doing within the profession there are others that are still evolving. The push for professionalisation of sports coaching has also led to an increased need to provide quality coach education. Many of the developments in this area have focused on the 'what' to deliver within these sessions, with minimal focus on the 'how' to deliver it. This paper attempts to synthesize the current literature in coaching and coach education as a means to assess if a signature pedagogy exists. Further we aim to highlight the key components that can be further researched to ascertain the strength of a potential signature pedagogy.